2013
DOI: 10.1111/pace.12212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Catheter Ablation for Long‐Standing Persistent Atrial Fibrillation in Women

Abstract: Women and long AF duration were closely related to the recurrence of AF after the first ablation in patients with long-standing persistent AF. Women also had a higher risk of vascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
5
44
0
Order By: Relevance
“…7,9,10,15 In studies showing reduced procedural success in women, worse outcome has primarily been attributed to more persistent forms of AF and more advanced structural remodeling at the time of ablation. 7,9 Patel et al retrospectively analyzed a large cohort (3265 patients, 16% women), with a lower prevalence of paroxysmal AF (46%) and higher prevalence of long-standing persistent AF (27%) in female patients.…”
Section: Rhythm Outcomementioning
confidence: 98%
See 2 more Smart Citations
“…7,9,10,15 In studies showing reduced procedural success in women, worse outcome has primarily been attributed to more persistent forms of AF and more advanced structural remodeling at the time of ablation. 7,9 Patel et al retrospectively analyzed a large cohort (3265 patients, 16% women), with a lower prevalence of paroxysmal AF (46%) and higher prevalence of long-standing persistent AF (27%) in female patients.…”
Section: Rhythm Outcomementioning
confidence: 98%
“…This is consistent with reports from previous studies. 7,10,18 Underlying reasons may be sex-specific anatomical varieties with close location or overlap of groin vessel branches in women and smaller vessel diameters. 19,20 Smaller left atrial chamber size may render intracardiac catheter navigation more difficult.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…252,289,290,291,806,808,920,1050,1051,1052,1053,1054,1056,1057,1058,1059 A multicenter U.S. retrospective study reported total complications of 3265 (518 in women vs 2747 in men), with a 5% complication rate in women vs 2.4% in men ( P <.001). This study found more hematomas and pseudoaneurysms in women.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…Only 1 study evaluated the outcome for women after CA of persAF which revealed higher recurrence rates as shown in our study. 43 …”
Section: Female Sexmentioning
confidence: 99%